ANTIBACTERIAL ACTIVITY OF RADIATION DEGRADED CARBOXYMETHYL CHITOSAN - TRAN , MINH QUYNH; NGUYEN , DUY LAM; FUMIO , YOSHII (Nuclear Science and Technology, 2012)
In this study, 10% aqueous solutions of carboxymethyl chitosan was irradiated at various doses using 60Co gamma source and radiation effects on its viscous average molecular weight were determined. In addition, carboxymethyl chitosan powder also irradiated with the same dose for comparison. Antimicrobial activities of carboxymethyl chitosan and its irradiated samples were investigated against Escherichia coli and Pseudomonas fruorences. The bacteria were cultured in the nutrient medium supplementing irradiated carboxymethyl chitosan, then optical density of culture fluid was measured using a turbidity. The results indicated antimicrobial activity of irradiated carboxymethyl chitosan not only depends on its concentration, but also depends on radiation dose, namely its molecular weight. The highest antimicrobial activity was observed for carboxymethyl chitosan irradiated at 100 kGy. This has been suggested that irradiation can be applied to improve the antimicrobial activity of carboxymethyl chitosan.